Intensification of heat exchange with a modified coolant in phase transition heat accumulators - Vankov Yuri; Ponomarev Roman; Timershin Azat; Sharafiev Dmitriy (E3S Web of Conferences)
The article presents the results of experiments on intensifying heat transfer of a paraffin heat accumulator using nanomaterials. The purpose of the work is to create a laboratory stand to test the effectiveness of a heat accumulator using a nanomodified coolant. The paper presents information about phase transition heat accumulators, a description of the laboratory bench, and the results of experiments. During the study, results were obtained that allowed us to evaluate the positive effect of the introduction of nanomodifiers on the operating cycle of a heat accumulator.